Semivariational numerical model of pre linear filtration with the special emphasis on nonlinear sources - Schaefer, Robert; Sędziwy, Stanisław (Computer Assisted Methods in Engineering and Science; Vol 3 No 2 (1996), 2023)
The initial- boundary value problem for quasi- linear parabolic equation with distribution coefficient modeling the nonlinear filtration is discussed. The presented results constitute extension of the earlier works of the authors concerning the filtration problem in the domains without sources to the case of filtration in the presence of sources.